In Sickness and in Health: Job Displacement and Health Spillovers in Couples - Gathmann, Christina; Huttunen, Kristiina; Jernström, Laura; Sääksvuori, Lauri; Stitzing, Robin (The Review of Economics and Statistics, 2025)
Abstract Using administrative labor market data matched to mortality statistics and patient records, we document that negative labor market shocks produce sizable health spillovers in couples. For every 100,000 displaced men, there are 1,100 additional deaths. Of those, 60% accrue to the displaced worker, but 40% are due to excess spousal mortality. We find a stunning gender asymmetry: while male job displacement generates persistent negative health effects, no such dire consequences are observed after a woman’s job loss. We explore several explanations for these patterns: risk sharing through spousal labor supply; earnings losses and public insurance; widowhood; regional mobility and gender roles in the family.